2012
DOI: 10.3390/mi3020295
|View full text |Cite
|
Sign up to set email alerts
|

Design Issues for Low Power Integrated Thermal Flow Sensors with Ultra-Wide Dynamic Range and Low Insertion Loss

Abstract: Flow sensors are the key elements in most systems for monitoring and controlling fluid flows. With the introduction of MEMS thermal flow sensors, unprecedented performances, such as ultra wide measurement ranges, low power consumptions and extreme miniaturization, have been achieved, although several critical issues have still to be solved. In this work, a systematic approach to the design of integrated thermal flow sensors, with specification of resolution, dynamic range, power consumption and pressure insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…In some applications, the interconnection tracks were made of semiconducting materials such as polysilicon. Recently, Brushi et al reported that the static thermopile voltage is strongly affected by thermopile-heater spacing for various heater interconnection materials [ 22 ]. Polysilicon has been widely used as heater and temperature sensing material for the detection of hazardous gases in automotive exhaust control.…”
Section: State Of the Art Materials And Properties For Harsh Envirmentioning
confidence: 99%
See 1 more Smart Citation
“…In some applications, the interconnection tracks were made of semiconducting materials such as polysilicon. Recently, Brushi et al reported that the static thermopile voltage is strongly affected by thermopile-heater spacing for various heater interconnection materials [ 22 ]. Polysilicon has been widely used as heater and temperature sensing material for the detection of hazardous gases in automotive exhaust control.…”
Section: State Of the Art Materials And Properties For Harsh Envirmentioning
confidence: 99%
“…Thermal flow sensors more often find applications in harsh environments than non-thermal flow sensors because of their fast response and the lack of moving parts. The advances in Micro-Electro-Mechanical Systems (MEMS) technology allows for the fabrication of miniaturized thermal flow sensors with extraordinary performance in terms of sensitivity, response time, cost-effectiveness and power consumption [ 22 ]. Among the various semiconductor sensors, silicon-based sensors play a significant role in many applications and numerous silicon flow sensors have been developed [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…is strongly affected by thermopile-heater spacing for various heater interconnection materials. [20]. Polysilicon has been widely used as heater and temperature sensing material for the detection of hazardous gases in automotive exhaust control.…”
Section: Metals and Alloysmentioning
confidence: 99%
“…Thermal flow sensors more often find applications in harsh environments than non-thermal flow sensors because of the fast response and the lack of moving parts. The advances in Micro-Electro-Mechanical Systems (MEMS) technology allows for the fabrication of miniaturized thermal flow sensors with extraordinary performance in terms of sensitivity, response time, cost-effectiveness and power consumption [20]. Among the various semiconductor sensors, silicon-based sensors play a significant role in many applications and numerous silicon flow sensors have been developed [21].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades different designs and configurations have been proposed by the researches in this field. Bruschi et al [14] published a study on the issues of the integrated calorimetric micro-sensors illustrating their advantages as well as their limitations and their problems.…”
Section: Calorimetricmentioning
confidence: 99%